Africa Multiple connects ... - Africa Multiple Cluster of Excellence; Universität Bayreuth - Institut für Afrika-Studien (2020)
The overarching aim of the series is to advance the study of Africa and its diasporas through offering a forum for multidisciplinary research. The peer-reviewed series is designed to overcome existing power imbalances in the production and transmission of knowledge in African Studies. Encouraging critical reflections on area studies, the series seeks to set new standards for collaborative research in the field, informed by an understanding of Africa as multiple that emphasizes relationality and reflexivity as its main conceptual approaches. The series invites contributions from diverse fields and disciplines, ranging from social sciences, cultural studies and humanities to law, geography and beyond. As part of the programmatic objective of reconfiguring African Studies, we include publications in English as well as other academic languages (such as French, German, Kiswahili, Arabic, and Portuguese)